Pengembangan Kamus Biologi Bergambar pada Materi Kingdom Animalia Mata Pelajaran Biologi untuk Sekolah Menengah Atas - Jayanti Jayanti; Vivi Sisca; Eko Wulandari (BIOCOLONY, 2022)
This research is motivated by the lack of an illustrated biological dictionary in SMA N 10 Sarolangun, students have difficulty in interpreting Latin terms or scientific language in the package book, but students can interpret biological terms through the glossary in the package book, the glossary contained in the package book is not complete, the average existing biological dictionary is not equipped with pictures. This study aims to develop an Illustrated Biology Dictionary on Kingdom Animalia Biology Subject Matter for High School that is valid and practical. The development of this dictionary uses the R&D method with the 4-D model which consists of the define, design, develop, and disseminate stages. The subjects of this study consisted of 5 validators, for the practicality test conducted by 1 Biology teacher and 10 students of class X SMA N 10 Sarolangun. The data from this study are the results of the validity and practicality of the dictionary, then this data is analyzed by descriptive analysis. Based on the results of this study, a product in the form of an illustrated biological dictionary of animal kingdom material was produced. The product developed was declared very valid by validators both from the aspects of content feasibility, language, presentation, and graphics with an average validity value of 90%. The product was also declared practical by teachers while by students it was declared very practical both from the aspects of ease of use, learning time, and attractiveness with an average value of 3.35 by teachers and 3.92 by students. So that the illustrated biological dictionary has been declared valid and practical.